Cognitive transformation, social ecological settings, and the reentry outcomes of women offenders - Berg, Mark T. (Crime & delinquency, 2017)
Of theoretical interest to research on reentry and desistance is the intersection of cognitive transformation and the ecological contexts to which offenders return. The majority of offenders released from prisons in the United States return to impoverished neighborhood settings. However, there is a limited understanding of how offenders with different cognitive commitments to change interpret and negotiate the prosocial and illicit features situated in their environments. Drawing on different lines of theoretical research, we examine how cognitive commitments are affected by the lures and prosocial features of impoverished neighborhoods and how the intersection of these conditions affects success and failure in the post-release period. We use original survey and in-depth qualitative interviews with 37 incarcerated and formerly incarcerated women from St. Louis, Missouri. Findings suggest that an integrated examination of cognitive mechanisms and residential environments clarifies how offenders who return to similarly structurally disadvantaged places exhibit different reentry outcomes.